Pre-service English teachers' experience with various CALL applications: Hindrances and reflection - Syafryadin Syafryadin; Veronika Unun Pratiwi; Dian Eka Chandra Wardhana (Universitas Syiah Kuala, 2021)
Computer assisted language learning (CALL) is one of the alternative ways used by teachers in teaching English. This research aims to find out various CALL applications used by the pre-service English teachers, the difficult skills faced by students, hindrances, and pre-service teachers’ reflection. A mixed-method approach with questionnaires, interviews guideline, and observation checklist were employed by the researchers. The sample consisted of 30 pre-service English teachers and 750 students. The data analyses were done by using simple statistics calculations, codes, and categories. The results showed that pre-service English teachers applied various CALL applications, in which the majority of them used Hello English for speaking in the classroom because of the ease of use of the application. The most difficult skills learned by students were listening, and the easiest skill was reading. Another finding is related to hindrances during CALL applications which included internet connection, material understanding, CALL application procedures, assessment, discipline, cost, and learning style. However, those problems were eventually solved by pre-service English teachers. Furthermore, pre-service teachers wrote their teaching reflection to know their evaluation of their teaching. The reflections showed that they could solve the problems, made, and revised lesson plans, and brought good role models in the classroom.